The study of forward and reverse schottky junction for dual magnetodiode - Phetchakul, T.; Luanatikomkul, W.; Yamwong, W.; Poyai, A. (My University, 2012)
This paper presents schottky diode for sensing magnetic field. The structure is the same as dual magnetodiode that had been reported by the same group. The device can operate both in forward and reverse biasing for magnetic field device. The sensitivity (ΔV o/ΔB) by simulation of forward bias is 0.8 mV/T at the current 1.93 μA and reverse bias is 6 nV/T at the current 13.49 pA. Two modes of operation show linearity which electron is the only type of carrier. The mechanism of forward and reverse modes of operation are described. © 2012 IEEE.
Keywords: Magnetodiode; Schottky junction; Sentaurus TCAD